Breed and anatomical predisposition for canine cutaneous neoplasia in South Africa during 2013. (22nd February 2020) - Tompkins, Samantha; Fosgate, Geoffrey T; Williams, June; Clift, Sarah
Abstract : Cutaneous neoplasia occurs commonly in dogs and owners in consultation with their veterinarian must decide when to perform surgery to obtain a histopathological diagnosis. The objective of this study was to identify breed predispositions for canine cutaneous neoplasms and determine factors associated with malignancy. This retrospective case‐series evaluated histopathology reports from two veterinary pathology laboratories in South Africa during a six‐month study period. Breed predispositions were analysed using log‐linear models and risk factors for malignancy were evaluated using binary logistic regression. Data were available for 2553 cutaneous neoplasms from 2271 dogs. The most frequent neoplasms were mast cell tumours (21.1per cent), histiocytoma (9.4per cent), haemangiosarcoma (8.3per cent), melanocytoma (5.8per cent) and lipoma (5.1per cent). Boxers (relative proportion (RP)=38.9; 95% CI 2.3 to 646), pugs (7.6; 1.4 to 41.0), Staffordshire bull terriers (7.0; 1.9 to 26.3), boerboels (3.8; 1.3 to 10.7), Labrador retrievers (2.7; 1.0 to 7.0) and mixed breed dogs (2.2; 1.1 to 4.4) had a higher frequency of mast cell tumours. Jack Russell terriers (OR=2.5; 95% CI 1.8 to 3.5), Rottweilers (2.3; 1.3 to 3.9), pit bull terriers (2.2; 1.1 to 4.3) and Staffordshire bull terriers (1.6; 1.0 to 2.6) were more likely to have malignant neoplasms. Dog signalment might facilitate prognosis determination for cutaneous canine neoplasia before receiving a histopathological diagnosis.